Influence of 4′-Substitution on the Activity of Gemcitabine and Its ProTide Against VZV and SARS-CoV-2 - Zheng, Zihua (ACS Med Chem Lett, 2020)
[Image: see text] In addition to its therapeutic value as a chemotherapy drug, gemcitabine is of ongoing interest to the scientific community for its broad-spectrum antiviral activity. Herein the synthesis of 4′-methoxy- and 4′-fluoro-substituted gemcitabine analogues along with their phosphoramidate prodrugs is described. Among these derivatives, 4′-fluorogemcitabine proved to be active against varicella zoster virus (VZV, TK+ strain) with an EC(50) of 0.042 μM and produced significant cytotoxicity (CC(50) = 0.11 μM). Upon derivatization of this trifluoro nucleoside as its prodrug, decreased anti-VZV activity was observed, but with a concomitantly improved selectivity index (SI = 36). When this prodrug was tested against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), its antiviral activity (EC(50) = 0.73 μM) was comparable to or slightly lower than its cytotoxic concentration in measurements of cell growth and cell morphology, respectively.